The COVID-19 Pandemic: Role of Coping Humor and Internal Health Locus of Control on Social Dysfunction and Anxiety & Depression - Sumantri, Muhammad Arief; Zahrani, Zahrani; Ainiyah, Hilda Rosa; Idham, Azmul Fuady (Kesmas, 2021)
The concerns about the impact of social distancing on mental health have been widely discussed. This study aimed to know the predictive effect of coping humor and Internal Health Locus of Control (Internal HLoC) on social dysfunction and anxiety & depression during the implementation of the COVID-19 social distancing agenda. This study was also intended to assess the effect of humor content on coping humor. A quantitative approach was used as the method ofthe study with 243 online-recruited participants, and a PLS-SEM analysis was applied to find out the predictive effect in this study. The results and conclusions showed that anxiety & depression predict social dysfunction (β = 0.584, t-value = 11.93, f2 = 0.563). It was found that coping humor was able to directly increase the Internal HLoC (β = 0.187, t-value = 2.60, f2 = 0.036) and indirectly decrease social dysfunction (β = -0.144, t-value = 2.85) and anxiety & depression (β = -0.070, t-value = 2.42). Humor content unrelated to the issue of COVID-19 directly increase the coping-humor level (β = 0.266, t-value = 4.13,f2= 0.076), and indirectly increase Internal HLoC (β = 0.050, t-value = 2.07), and decrease anxiety & depression level (β = -0.046, t-value = 2.20). On theother hand, Internal HLoC directly decrease levels of social dysfunction (β = -0.233, t-value = 4.126, f2 = 0.089) and anxiety & depression (β = -0.373, t-value= 7.84, f2 = 0.161).